Building brand communities : how organizations succeed by creating belonging - Jones, Carrie Melissa; Vogl, Charles H. (Berrett-Koehler Publishers, 2020)
"An authentic brand community is more than just people buying your product or working alongside one another. This book articulates the critical roles of mutual concern, common values, and shared experiences in creating fiercely loyal customer and collaborator relationships"--